Analisis Makna Gaya Bahasa Personifikasi Puisi Hujan Bulan Juni karya Sapardi Djoko Damono - Winarti Winarti S.Pd., M.Pd (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The literary style is the style of the author in using language to get the effect of a more beautiful and attractive. In the poem titled Sapardi Djoko Damono rains in June had a wonderful personification of style and gives the effect of calm, peaceful, and full of harmonica in the reader once read. This poem about longing for the infinite meaning of a character named Rain in June to a figure called the Tree. Rain was very patient in secret longing, but very dense and intense longing. But the rain also wise in maintaining longing, he had wanted to declare missed it but because there is no doubt that is why he canceled the traces of its business. In addition to patient and wise, rain also has a sensible nature. Not a single person in this world setabah, wisely, and searif Rain. In the case wisely, he shall mengikhlaskan longing to be restored to God and nature. Ikhlas is a wise final decision in the store feeling. Rain hope someday, trees can know that there is always a longing in every speckled bushy trees that bloom to it.